2009
DOI: 10.3905/jod.2009.17.1.062
|View full text |Cite
|
Sign up to set email alerts
|

Mr. Madoff’s Amazing Returns: An Analysis of the Split-Strike Conversion Strategy

Abstract: It is now known that the very impressive investment returns generated by BernieMadoff were based on a sophisticated Ponzi scheme. Madoff claimed to use a splitstrike conversion strategy. This strategy consists of a long equity position plus a long put and a short call. In this paper we examine Madoff's returns and compare his investment performance with what could have been obtained using a split-strike conversion strategy based on the historical data. We also analyze the split-strike strategy in general and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…He found that Madoff's high and smooth returns were too good to be true. These findings are detailed in Markopolus (2005) and are confirmed by Bernard and Boyle (2009) and Culp and Heaton (2010).…”
Section: Literature Reviewsupporting
confidence: 57%
“…He found that Madoff's high and smooth returns were too good to be true. These findings are detailed in Markopolus (2005) and are confirmed by Bernard and Boyle (2009) and Culp and Heaton (2010).…”
Section: Literature Reviewsupporting
confidence: 57%
“…Schemers usually states that a return on investment is a result of sound investment (Deason et al, 2015) or a result of applying a specific investment strategy. Bernard Madoff, for example, stated that he used a split-strike investment strategy to manage investor funds (Bernard and Boyle, 2009;Clauss et al, 2009;Gregoriou et al, 2009). Even though there is no agreement on the definition of Ponzi and pyramid schemes (Eisenberg and Quesenberry, 2014), in some definitions, both systems can be defined as "investment schemes that promise high or definite returns to investors but return given to investors is purely from funds deposited by other investors".…”
Section: Ponzi and Pyramid Schemesmentioning
confidence: 99%
“…For example, Madoff's largest investors, such as Fairfield Greenwich, viewed themselves equally as victims in his fraud, despite having apparently failed to notice red flags or reportedly perform required due diligence. However, various studies argue that Madoff investors could easily have discovered the fraudulent nature of the returns series by performing operational due diligence or quantitative analysis (e.g., Bernard and Boyle, 2009;Clauss et al, 2009;Gregoriou & Lhabitant, 2009). The same point is made in the many lawsuits filed by the court-appointed trustee, Irving Picard, charged with recovering money for Madoff's victims inter alia against even such large and reputable banking institutions as HSBC and J P Morgan (Masters, 2010;Masters et al, 2011).…”
Section: Hedge Funds and The Intrusion Of Realitymentioning
confidence: 99%